The immediate futures of health law after Brexit: Law, 'a-legality' and uncertainty. (June 2018) - Hervey, Tamara; Speakman, Elizabeth M
The European Union (EU) is a rules-based international organisation with an exceptionally dense legal system. Likewise, the ways in which EU law has effects in domestic law are determined by (constitutional) law. The legal rights and obligations entailed for state and 'third sector' entities, companies and human beings of some 45 years of membership have had significant effects on domestic health law across the United Kingdom, even though health per se is a national competence. That said, the EU's relationships with national legal orders are also determined by the politically possible. We therefore sketch the key legal questions for UK health law, and health law in each of the 'devolveds', in two possible immediate post-Brexit futures. By immediate future, we mean after 29 March 2019, the date on which the Article 50 TEU notification period ends. It will not be possible to answer these legal questions until the politics have crystallised into legal texts, which is not the case at the time we write. We go on to argue that the ways in which UK health law, policy and practice are currently determined by the UK's membership of the EU, coupled with the short time frame within which the future EU-UK relationship must be determined, mean that law may be expected to be less of a determinant in immediate post-Brexit futures than it is at present. Our principal conclusion is that the uncertainties that surround the process of Brexit mean that at a level of specific policy and practice, such as in areas of health law, we might expect a period of 'a-legality', where the legal position of actors does not necessarily determine or explain their actions.